Biodiversity of flora in the lower basin of the Reque river - Arbulú Chereque, Edgardo Pedro Rodolfo (2021)
To measure the biodiversity of flora in the lower basin of the Reque river, 8 perpendicular transects were traced at distances of 10 x 250 m on each side of the Reque river bed from 20 to 30 October 2020. In them, flora species were identified; The number of specimens per species and transect were recorded in a Microsoft 2013 Excel spreadsheet, saved with the csv extension delimited by commas. The Species Diversity and Richtnes and PAST software were used to determine Alpha and Beta Biodiversity Indices. It was concluded that the most abundant plant families were Fabaceae with species of Prosopis sp (algarrobo); Acacia huarango (huarango), Crotolaria incana; Cajanus cajan (stick beans) and Inga Fewelei (guava) and Saccharum officinarum (sugarcane Distichlis spicata (salty grass), Zea mays (corn) and Sorghun halepensis (sorghum) of the Poaceae family. The Shannon-Wiener index varied from 1,956 in the D transects to 3,437 in the H transects with an average value of 3,271. The Pielou equity index ranged from 0.4427 in the C transect to 0.7777 in the H transect. The Q statistic ranged from 3.474 to 22,38. The Beta Biodiversity indices were: Whittaker Bw Index 1,594; Cody Bc Index = 43.5; Routledge Br Index = 0.3256 and Wilson & Schmida Index = 1.359. The determined indices reached values that allow considering this area has a high floristic biodiversity.